From Age to Age : How Christians Have Celebrated the Eucharist, Revised and Expanded Edition - Foley, Edward (Book collections on Project MUSE., 2008)
"Eucharist is the fullest expression of our life with God, a life we share with Christians throughout the ages. It is also a sensory experience, engaging us in the sights and sounds, tastes and touch of the worship. Edward Foley's revised and expanded From Age to Age draws readers into that sensory experience. He traces the development of Christian Eucharist from its Jewish roots to our own time. In addition to exploring the architecture, music, books, and vessels that contributed to each period's liturgical expressions, this edition introduces readers to the theology of each age as well as the historical and cultural contexts that shaped the Eucharist. Richly illustrated with numerous images and quotations from period texts, this book is a feast for the mind and eye. Through many examples of the visual and auditory symbols that are central to Eucharist, readers will discover how Christian worship is embodied worship that from age to age gives glory to God and sanctifies people."--BOOK JACKET.